Recent Advances in Synthesis and Study of 2D Twisted Transition Metal Dichalcogenide Bilayers. Issue 5 (10th March 2021) - Tang, Bijun; Che, Bingyu; Xu, Manzhang; Ang, Zhi Peng; Di, Jun; Gao, Hong-Jun; Yang, Haitao; Zhou, Jiadong; Liu, Zheng
Abstract : In recent years, twisted 2D transition metal dichalcogenides (TMDs) have attracted tremendous research interest thanks to their intriguing properties that are essential in developing future electronic and photoelectronic devices in this modernizing era. The aim of this review is to introduce recent developments in the preparation of twisted TMD (t‐TMD) bilayers, their properties investigated by photoluminescence (PL) spectroscopy, Raman spectroscopy, and other techniques, as well as the related distinctive physical phenomena. First, various strategies for synthesizing t‐TMD bilayers via the two‐step stacking method and one‐step chemical vapor deposition method are reviewed. Then, the commonly used characterization techniques in probing the interlayer coupling between the twisted layers are introduced. Moreover, the intriguing physical properties associated with twisting such as interlayer excitons and correlated electronic phases are summarized. Last but not least, challenges and future research directions are briefly discussed in light of recent advances in the field. Abstract : Development of twisted 2D materials with intriguing properties is essential for the construction of future electronic and photoelectronic devices. Herein, the recent progress in the study of twisted transition metal dichalcogenides in terms of preparation, characterization, and physical properties is reviewed. Challenges and perspectives are briefly discussed.